From fullerene acceptors to non-fullerene acceptors: Prospects and challenges in the stability of organic solar cells - Speller, Emily M.; Clarke, Andrew J.; Luke, Joel; Lee, Harrison Ka Hin; Durrant, James R.; Li, Ning; Wang, Tao; Wong, Him Cheng; Kim, Ji Seon; Tsoi, Wing Chung; Li, Zhe (Journal of Materials Chemistry A, 2019)
The recent emergence of non-fullerene small molecule acceptors has reinvigorated the field of organic solar cells, already resulting in significant breakthroughs in their power conversion efficiency and discovery of remarkable new science. The stability and degradation of this class of materials and devices, on the other hand, has to date received relatively less attention. Herein, we present a critical review into the fundamentally different degradation mechanisms of non-fullerene acceptors compared to fullerene acceptors, as well as the very different roles they play upon the charge carrier generation and recombination kinetics and the resulting solar cell stability. We highlight in particular the prospect of the emergence of non-fullerene acceptors in addressing several major degradation mechanisms related to the use of fullerene acceptors, in conjunction with a number of unique degradation mechanisms that only exist in non-fullerene acceptors, which would provide an important guideline for further developments toward achieving long-term stability of organic solar cells.
CRIS-Team Scopus Importer:2019-11-05